Análise do impacto do ajuste a valor justo dos ativos biológicos no resultado anual - Serraglio, Ederson Luiz (Universidade do Vale do Rio dos Sinos, 2016)
In 2009 the pronouncement of the Accounting Pronouncements Committee (CPC) 29, about Biological Assets and Agricultural Products, changed the accounting of these assets by companies. Among the changes are the periodic evaluation and the necessity of measurement at fair value. A natural consequence of this amendment proposed by CPC 29 is that the measurement at fair value causes variability of the biological assets through profit or loss. These gains or losses since then are applied immediately to the annual result. The objective of this study is to analyze the impact of measurement at fair value of biological assets in the annual results. Using a sample of 41 companies that had biological assets in their financial statements in the period 2010 to 2014, being 25 public companies and 16 privately held companies listed in the 500 biggest and best according to Revista Exame. The research analyzed the financial statements, especially the notes, and the hypotheses were tested using statistical and econometric techniques. Results show that the use of measurement at fair value of biological assets causes a positive impact on the annual result, and that the analyzed companies do not used this adjustment mechanism of its biological assets to change their results. The results also show that the adjustment mechanism alone does not produce an increase in the volatility of results of the companies, but that the adjustments are affected by fluctuations in the prices of the products marketed by these companies. Thus, it is considered that the study contributes to show the influence of the use of the measurement at fair value of biological assets in the annual results of companies.
Keywords: Ativo biológico; Ajuste a valor justo; Resultado anual; Custo histórico; Biological assets; Adjustment to fair value; Annual result; Historical cost; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis